Selection and Validation of the Most Suitable Reference Genes for Quantitative Real-Time PCR Normalization in Salvia rosmarinus under In Vitro Conditions - Rohit Bharati; Madhab Kumar Sen; Ram Kumar; Aayushi Gupta; Vishma Pratap Sur; Ingrid Melnikovová; Eloy Fernández-Cusimamani (Plants, 2022)
Salvia rosmarinus L. (rosemary) is known to have a wide range of pharmacological effects including antidiabetic, anticarcinogenic, and antitumorigenic properties owing to its secondary metabolites. Studies aiming to elevate these metabolites have utilized various elicitors and stresses under in vitro conditions, although underlying molecular mechanisms remain unexplored. Gene expression studies using RT-qPCR might provide valuable information regarding how plant and plant cells interact and perceive various treatments and elicitors. However, despite being able to calculate accurate fold changes, the accuracy of the RT-qPCR data highly depends on the expression of reference genes. To the best of our knowledge, there is no information available on the stable reference genes in rosemary under in vitro conditions. Thus, in this paper, we assessed the stability of seven commonly used reference genes under different elicitor and stress conditions using RT-qPCR. Thereafter, the five most commonly used software and algorithms (comparative ΔCt, BestKeeper, NormFinder, geNorm, and RefFinder) were used to rank the candidates based on their expression stabilities. In conclusion, we recommend using a combination of F1-ATPase, ATP synthase and ACCase to normalize the gene expression experiments in rosemary under in vitro conditions. The selected reference genes were verified using 4-coumarate-CoA ligase, a pharmacologically important gene, whose expression might alter under nanoparticle treatment. Additionally, reference genes for several plant tissues, elicitors, and stresses are also proposed. The conclusions obtained from this current study will accelerate the future molecular work in S. rosmarinus and other related species.